710 IPC STOCKINGS FOR VTE PREVENTION IN STROKE: BENEFITS OF INTRODUCING ELECTRONIC PRESCRIPTIONS AND WARD ROUND PROMPTS. (8th March 2022) - Ross, K; Kattakayam, F; Hall, E; Barker, J R
Abstract: Background: A fully completed audit cycle, performed by doctors on the Stroke Unit at Royal Lancaster Infirmary (RLI) which is a combined acute and rehabilitation ward in a university teaching hospital. Introduction: Deep vein thrombosis (DVT) and pulmonary embolism (PE) are common complications of hemiplegic stroke. Evidence shows that IPCs (intermittent pneumatic compression devices) reduce the risk of DVT. Recent data from SSNAP reports that IPCs are only used in 33% of all stroke patients. We aimed to improve our local standards in the prescription of IPCs for stroke patients within 3 days of admission, thus reducing the incidence of VTE (venous thromboembolism). Methods: Data was collected retrospectively from patient records of all stroke patients discharged over a one-month period for each of 2 audit cycles. Prescribing is electronic based at RLI. After the first cycle we initiated a prompt on the electronic VTE pro forma to initiate prescribing. We also changed the prescribing default to regular instead of when required, requiring staff to document when they were not given and the reasons why. Results: Between the first and second cycle, completion of VTE proformas improved to 100% and VTE incidence reduced from 7.6% to 0. Overall, there was a large improvement in prescribing IPCs within the first 3 days of admission. 71% of patients reviewed in the second cycle had IPCs prescribed compared to 37% in the first. Conclusion: Adherence to local standards in prescribing of IPCs within 3 days of admission markedly improved after the Introduction of electronic ward round prompts and prescriptions and the incidence of VTE decreased to zero. The prescribing prompts encouraged increased documentation of administering of IPCs. There are still some issues concerning documentation and prescribing of anticoagulants which will be tackled by implementing teaching sessions and updating our electronic prescribing prompts.